Lipid anthropometric and physical condition profile of university athlete students - García Cardona, Diana María; Sánchez Muñoz, Oscar Eduardo; Cabrera Arismendy, Carlos Enrique; Restrepo Cortés, Beatriz (Universidad y Salud, 2017)
Introduction: Recognizing aspects such as lipid profile, body composition and physical composition of athletes can avoid recurrent errors in sports training. Objective: To establish the lipid, anthropometric and physical condition profile of students belonging to the sports teams of the University of Quindío. Materials and methods: Members of 14 sports teams were valued in their anthropometric measurements according to the guidelines of the International Society for the Advancement in Kinanthropometric (ISAK). For this, different tests were applied to determine strength, speed, resistance and flexibility and commercial kits were used to establish the lipid profile. Results: The population has normal ranges of lipid profile. Regarding the anthropometric profile, averages of fat percentage were found above those that are considered normal for athletes, although they correspond to the normality of the population in general. On a conditional level, flexibility was the capacity with lower averages from those considered as acceptable ranks. Conclusions: It is necessary to look for strategies to improve aspects such as: levels of fatty percentage and flexibility, which in some participants are not in line with the established ranges for performance athletes.